Etiology and diagnosis of gummy smile - Literature review (Research, Society and Development, 2021)
A smile represents, besides a form of communication, a means of socialization. The symmetry of a smile consists not only in the harmony between shape, position and color of teeth, but also in the balance between face, lips and gum tissue. The "gummy smile" is characterized by exaggerated gingival exposure, resulting in an un-aesthetic smile. This condition can arise as a result of one etiological factor, or by the combination of several of them, such as skeletal, dental, labial, periodontal or external alterations. It is essential that the dental surgeon knows its etiological factors in order to make a correct differential diagnosis. The objective of this study is to explore the concept, etiology, classification, and diagnosis of the gummy smile, through a literature review. Searches were performed in the Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL), US National Library of Medicine National Institutes of Health (PubMed) and Google Scholar databases. According to the data available in the literature, it can be concluded that a correct diagnosis is essential to draw an individualized treatment plan, with satisfactory long-term results that meet the patient's aesthetic and functional expectations. Therefore, the dental surgeon should be able to identify the causes of gummy smile and define the predominant etiologic factor in each case.